Determinação de Al, Cu, Fe, Pb e Zn em amostras de alcachofra e catuaba por espectrometria de absorção atômica - Deyse de Brito Marthe (2011)
Medicinal plants are used to prevention and treatment of diseases by the population. To ensure the safety, efficiency and quality control of herbal medicines, it is necessary to know its effects on human health, and also provide the mineral composition of these plants. The elements in plants can be explained by several factors, such as geological and climatic conditions that depend on their concentration in soil, human activities and type of plant species. However, the accumulation of metal ions possibly will be related to toxicity to the human body. In this work, it was analyzed leaves, extracts, tablets, capsules, and beverages from artichoke (Cynara scolymus L.) and catuaba (Trichilia catigua). The determination of aluminum, lead, copper, iron and zinc in these samples was realized by atomic absorption spectrometry with flame or graphite furnace after different strategies for sample pretreatment: microwave-assisted acid digestion, direct analysis and availability experiments using a solution that simulated gastric juice. A 23 full factorial design with central point was applied to study the effect of some variables, such as acid mixture, time and temperature in the digestion of artichoke leaves in the cavity-microwave oven. The digestion procedure was optimized and direct analysis of liquid samples for catuaba and artichoke were realized. Some results obtained after microwave acid digestion were compared to those obtained with the availability of elements in the digestive tract. Total concentrations, after microwave acid digestion were used as reference values to evaluate the efficiency of other proposed procedures. A NIST SRM 1573a was used to check the accuracy. Results were in agreement to the certificate values at 95% confidence level. The total concentration ranged considerably, but for copper and zinc in the catuaba power samples, the values were similar. Aluminium and iron were present in higher concentrations in most samples. For liquid samples, availability tests showed higher concentrations, when compared to the direct determination. However, after availability experiments, it was possible to figure out that these elements are not readily available in the samples investigated. For the metals investigated in the samples, the contents are within the limits allowed for consumption.